The Relationship Between Work Environment Factors, Communication, And Teamwork with The Implementation of Patient Safety Culture: A Literature Review - Agustini, Ni Luh Putu Inca Buntari; Wahyuni, Ni Komang Sri; Mahaputra, I Nyoman Arya; Putri, Ni Made Manik Elisa (Babali Nursing Research, 2025)
Introduction: A key component of quality management in the healthcare industry is the patient safety culture, which involves initiatives to prevent and reduce the likelihood of patient harm or injury during medical care. This literature review aims to explore the relationship between the implementation of a patient safety culture and factors such as work environment, communication, and teamwork. Method: This review was based on an analysis of published articles presenting findings from previous research. Using the search terms “patient safety culture” AND “factors” AND “work environment” AND “communication” AND “teamwork,” articles were retrieved from PubMed, ScienceDirect, and additional sources in Bahasa. A total of 17 articles met the inclusion criteria. The analysis employed a critical review approach to assess the strengths and limitations of the included studies, ensuring a comprehensive understanding of the current research landscape in this field. Result: The primary factors influencing a strong patient safety culture include teamwork, effective communication between supervisors and nursing staff as well as between departments, a supportive work environment, adequate nursing staff, and access to high-quality resources. Conclusion: Hospital management should prioritize improving patient safety culture through effective staff training programs, fostering clear and efficient communication, promoting teamwork, and ensuring a well-supported work environment.